The impact of poverty alleviation projects on households at Thulamela Municipality, Vhembe District - Radzilani, Humbulani Simon (University of Limpopo (Turfloop campus), 2006)
The purpose of the study was to identify material benefits that households participating in poverty alleviation projects receive. The study used both the qualitative and quantitative research design in the context of a random sample of 70 non-project households and 42 households participating in projects. A structured interview schedule was used to collect data. The major findings of this research study are that poverty alleviation projects are effective in alleviating poverty especially amongst rural women. The significance of the study lies in insights on improved methods in the management of poverty alleviation projects
Thesis (M.Dev.) --University of Limpopo, 2006
Keywords: Poverty alleviation; 362.570968; Poverty -- South Africa -- Limpopo; Economic development projects -- South Africa